Analisis Pencemaran Kualitas Air Sungai Bengawan Solo Akibat Limbah Industri di Kecamatan Kebakkramat Kabupaten Karanganyar - Ramadhani, Endi; , Dra. Alif Noor Anna, M.Si; , Drs. Munawar Cholil, M.Si (2016)
Pollution of the river water is often triggered by the increasing complexity of various human activities, including the activities of industrial production. Industrial activity in district Kebakkramat which produces liquid waste generally circulate water discharge to streams, which then leads to a decrease the water quality of Bengawan Solo River, marked by physical changes water into blackish-coloured and the onset of the smell on the water, which certainly gives the indication of degradation of water quality of the River, which also affect the intensity of the natural ability of the river water in the self purification process. The purpose of this study, namely: 1) identifies the distribution of water quality pollution of the Bengawan Solo River; 2) determines the point of self purification process; 3) evaluate water quality conditions of the Bengawan Solo River contaminated by water quality standards that have been set. The research method used was a survey of the field, namely by making observations and measurements directly in the field. River water sampling using a purposive sampling technique, taking into account the criteria pollutant sources and the distance of the pollution. Types of data used include primary and secondary data, in the form of a data stream network maps and administrative maps for the approximate location of the sample, as well as the results of the value of the concentration of each of the parameters, both physically and chemically obtained from direct measurements in the field and laboratory test results. As for the concentration value results analyzed with trend analysis techniques, which linking between the concentration of the element to identify the contamination with distance distribution of pollution, as well as determine distance of self purification process, While the evaluation of water quality standard used comparative descriptive analysis that compares between the conditions of the water quality of the river areas of research with water quality standard according to the Government Regulation Number 82 of 2001. The results showed that: 1) distribution of water pollution the Bengawan Solo River research area showed fluctuating pattern, where the four parameters are related of the contaminating waste level (TSS, BOD, COD, and Sulfides), have an increased concentration at the point 3 and 5, as well as a decrease in concentration in the point 4 and 6; 2) The process of self purification Bengawan Solo river water contaminated can occur which is characterized by a decrease in concentration in the point 4 and 6. But based on the phases of the process, has not yet reached the final phase of the process of self purification, the zone of clean water; 3) Based on Government Regulation Number 82 of 2001, showed that the water quality conditions of the Bengawan Solo River from the six parameters investigated, two of them (pH and Total Suspended Solid) as a whole meets the quality standards level I - IV, levels of Dissolved Oxygen showed a tendency the quality standard level III - IV and Chemical Oxygen Demand levels are only eligible at two locations streams, namely at point 1 (level III - IV) and the last location (point 6) meets the level IV. In addition, there are two parameters which overall are not qualified and exceed the specified threshold, namely Biological Oxygen Demand and Sulfide (H2S).